Impact of Carbon Emission Disclosure and Corporate Social Responsibility on Indonesian Manufacturing Companies - Dina Maria Kristari; Armanda Yusram Teruna (Pandawan, 2023)
This study aims to examine the effect of carbon emission disclosures (CED) and corporate social responsibility (CSR) on the financial performance of manufacturing companies in Indonesia. The research utilizes secondary data extracted from the financial statements and annual reports of companies listed on the Indonesia Stock Exchange (IDX) during the period from 2017 to 2019. The analysis employs multiple regression panel data using SPSS software to assess the relationships between variables. These findings contribute to the understanding of the relationship between environmental disclosure, corporate social responsibility, and financial performance in the context of manufacturing companies in Indonesia. The negative impact of carbon emission disclosure on financial performance highlights the importance of managing and reducing carbon emissions to enhance financial outcomes. Additionally, the non-significant effect of CSR on financial performance suggests that other factors might have a more significant influence on companies' financial success. Furthermore, when considered simultaneously, both carbon emission disclosure and corporate social responsibility demonstrate an influence on financial performance.